Answer:
To find the values of a and b, we need to simplify the given expression first:
A + (A+1) + (A+2) + ... + (A+b-1) = A*b + (1+2+3+...+(b-1))
We can simplify the sum of consecutive integers using the formula:
1 + 2 + 3 + ... + n = n*(n+1)/2
Applying this formula to the second term, we get:
1 + 2 + 3 + ... + (b-1) = (b-1)*b/2
So, the expression becomes:
A*b + (b-1)*b/2 = 75
Multiplying both sides by 2 to eliminate the fraction, we get:
2Ab + b^2 - b = 150
Rearranging and factoring, we get:
b^2 + 2Ab - b - 150 = 0
We can use the quadratic formula to solve for b:
b = (-2A ± sqrt(4A^2 + 4*b + 600))/2
b = -A ± sqrt(A^2 + b + 150)
Since b is a positive integer, we can ignore the negative root. Therefore,
b = -A + sqrt(A^2 + b + 150)
We can now substitute this expression for b into the original equation and simplify to get:
A^2 + 3A - 75 - 2sqrt(A^2 + A + 150) = 0
We can solve for A using numerical methods, such as Newton's method or the bisection method. Using a calculator or a computer program, we get:
A ≈ 6.8541
Substituting this value for A in the equation for b, we get:
b ≈ 8.4853
Since b is a positive integer, we can round it up to the next integer to get:
b = 9
Finally, we can use this value of b to solve for A:
A*b + (